Pendekatan Dakwah Dalam Membangun Mental Masyarakat Kota Surakarta - Mukhlis Fathurrohman (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2023)
Substantially, religious proselytizing can be divided into two agents. They are agent of social service and agent of social change. As the agent of social service, religious proselytizing tries to fix the system of human live in Islamic through the process of amar ma’ruf and nahi munkar. Religious proselytizing as the agent of social change is changing situation and condition of moslems from underdevelopment, ignorance, destitution, atheism, tyranny, godlessness, and many more which is to be fixed or diverted toward the progress of wisdom, prosperity, faith, orderliness, and many more. Surakarta City is one of city where has glory and golden history of Islam before the freedom of RI and beginning of freedom. The desire of the future of Surakarta City is to go back at Solo City like the past time, so that the glory of Islam must be built with revitalization the role of religious proselytizing in building Surakarta City. The condition of Surakarta City is very diverse. It needs creativity of delivering the massage of religious proselytizing, so that it can create the value of Islam theory in the society. Some of method and phenomenological in building Surakarta City, namely : Integrative Functional, Dialogue, Cultural Approach, Physiology Approach, Political Approach, Cooperation between the Institutions, and Building Public Opinion.